TEACHERS' LIFE EXPERIENCES IN DIFFERENTIATED LEARNING IN ISLAMIC RELIGIOUS EDUCATION: A PHENOMENOLOGICAL STUDY - Faiz Aswa Nazhan; Munawar Rahmat; Mohammad Rindu Fajar Islamy (Jurnal Cakrawala Pendas, 2026)
The diversity of student characteristics poses a challenge in Islamic Religious Education (IRE) instruction, particularly regarding the History of Islamic Civilization curriculum in elementary schools, where teaching practices still tend to be uniform. Although differentiated instruction has been extensively studied, research highlighting teachers’ real-world experiences in implementing it in the classroom remains limited. This study aims to explore teachers’ experiences in applying differentiated instruction to the teaching of the IRE. This study employs a qualitative approach with a phenomenological design involving one IRE teacher at an elementary school. Data were collected through in-depth interviews, classroom observations, and document analysis, and were subsequently analyzed using Interpretative Phenomenological Analysis. The results indicate that differentiated instruction is implemented concretely through grouping students based on learning style preferences (visual, auditory, kinesthetic), adapting tasks to students’ readiness levels, using varied media, and employing product-based assessments such as infographics, presentations, and role-plays. The findings also suggest that these strategies enhance student engagement, classroom interaction, and understanding of historical content.  This study contributes to our understanding of how differentiated instruction is implemented in Islamic Religius Education classrooms, particularly in the context of elementary schools, and serves as a practical guide for teachers in developing more inclusive and student-centered instruction that responds to student diversity.